Peran Benteng Rotterdam di Kota Makassar Sebagai Sumber Belajar Sejarah - Muh Anugerah Saputera; Mustari Bosra; Bahri Bahri (Phinisi Integration Review, 2022)
The purpose of this study is to describe and analyze about the role of the fort of Rotterdam as a source of learning history. This type of research uses descriptive qualitative research. Data was collected by means of participant observation, in-depth interviews and documentation. The validity of the data using the persistence of observations, triangulation of sources and detailed descriptions. The data analysis techniques used were: making small notes, grouping data, analyzing, presenting data and drawing conclusions. The results showed (1) Fort Rotterdam has been used as a historic site in the city of Makassar. In the 1970s this fort was renovated on a large scale and on 27 April 1977 the Makassar Archaeological Heritage Preservation Office was inaugurated, which is now known as the Cultural Heritage Preservation Center (BPCB) of South Sulawesi Province and based on the decision of the Minister of Culture and Tourism of the Republic of Indonesia, Rotterdam fort was designated as a Cultural Heritage Object in 2010 which is used as a center for culture, education, and a place for art and cultural performances, a place for historical tours, and a place to learn history. (2) Based on interviews with the fort management, as well as with educators, they said that they supported the Rotterdam fort being used as a historical learning resource for those who want to know and learn history. The government continues to make efforts so that historical sites can be preserved as a source of learning history. One example of the government's efforts to make this fort a source of learning is by setting up a BPCB office and the La Galigo Museum inside the fort complex and creating the “Museum Entrance School” program to raise awareness about the importance of history for future generations.Tujuan penelitian ini adalah mendeskripsikan dan menganalisis tentang peranan benteng Rotterdam sebagai sumber belajar sejarah. Jenis penelitian ini menggunakan penelitian deskriptif kualitatif. Pengumpulan data dilakukan dengan observasi partisipan, wawancara mendalam dan dokumentasi. Keabsahan data menggunakan ketekunan pengamatan, triangulasi sumber dan uraian rinci. Teknik analisi data yang dilakukan: membuat catatan kecil, mengelompokkan data, menganalisis, menyajikan data dan menarik kesimpulan. Hasil penelitian menunjukkan (1) Benteng Rotterdam telah dijadikan sebagai situs bersejarah yang ada di kota Makassar. Pada tahun 1970-an benteng ini telah dipugar secara besar-besaran dan pada 27 April 1977 diresmikan Kantor Balai Pelestarian Peninggalan Purbakala Makassar, yang kini dikenal dengan Balai Pelestarian Cagar Budaya (BPCB) Provinsi Sulawesi Selatan dan berdasarkan keputusan Menteri Kebudayaan dan Pariwisata Republik Indonesia, benteng Rotterdam ditetapkan sebagai Benda Cagar budaya pada tahun 2010 yang dijadikan sebagai pusat budaya, pendidikan, dan tempat pertunjukan seni dan budaya, tempat berwisata sejarah, dan tempat belajar sejarah. (2) Berdasarkan wawancara dengan pengelola benteng, maupun dengan tenaga pendidik mengatakan bahwa mereka mendukung benteng Rotterdam dijadikan sebagai sumber belajar sejarah bagi mereka yang ingin mengetahui dan belajar sejarah. Pemerintah terus melakukan upaya agar situs-situs bersejarah dapat terus dilestarikan sebagai sumber belajar sejarah. Salah satu contoh upaya pemerintah menjadikan benteng ini sebagai sumber belajar adalah dengan mendirikan kantor BPCB dan Museum La Galigo di dalam kompleks benteng dan membuat program “Museum Masuk Sekolah” untuk meningkatkan kesadaran tentang pentingnya sejarah bagi generasi-genarasi penerus bangsa.